SEA LEVEL CHANGES ALONG THE COASTS OF KEA ISLAND AND PALEOGEOGRAPHICAL COASTAL RECONSTRUCTION OF ARCHAEOLOGICAL SITES - Mourtzas, N.D (Bulletin of the Geological Society of Greece, 2010)
Sea level changes during the Upper Holocene submerged the coasts of Kea in three different phases about 5.50m, 3.90m and 1.50m respectively below the contemporary sea level thus causing sea transgression along the shores of Kea, which varied from 8m to 78m depending on the coastal morphology. These changes caused the alteration of the earlier morphology at coastal archaeological sites of the Island, as the prehistoric settlement of Ayia Irini and Classical period port of Karthaia, as well as, submerged under the sea areas of coastal human activity during antiquity, as the ancient schist quarry at Spathi bay. The study of historical, geomorphological and sedimentological data indicative of previous sea levels allow the paleogeographical reconstruction of the coasts during the period of human activities in these areas.